“Possibilities of early prevention of chronic kidney disease in patients with type 2 diabetes mellitus based on clinical and anamnestic data” (Texas Journal of Medical Science, 2024)
to study the possibilities of early prevention of CKD in patients with type 2 diabetes based on clinical and anamnestic data.